Bilan energetique d'une population naturelle de Crepidula fornicata dans le bassin de Marennes-Oleron - Deslous-paoli, Jean-marc; Heral, Maurice; Masse, H (Actes de colloques. Ifremer. Brest [ACTES COLLOQ. IFREMER.]. 1985, 1983)
An energy budget has been evaluated for a natural population of Crepidula fornicata living at low water of spring tides in the oyster farming basin of Marennes-Oleron. This budget of production was estimated according to the position along the chain. The average biomass for an individual representative of the population was equivalent to 1.87 Kjoules, and the annual consumption C was 20.08 Kjoules/year. The energy budget expressed in percent of energy consummates was: C = Pg + Pr + Ps + R + F; 100 = 4.6 + 1.6 + 0.8 + 48 + 45. This budget is compared with literature data on other herbivorous gastropods and with those calculated for Crassostrea gigas in the same locality. Un bilan énergétique a été calculé pour une population naturelle de Crepidula fornicata vivant à la limite inférieure de la zone intertidale dans le bassin de Marennes-Oléron. Le bilan de production est calculé en fonction de représentatif de la population de biomasse équivalente à 1,87 Kjoules, la consommation annuelle C est de 20,08 Kjou]os/an. Le bilan énergétique exprimé en pourcentage de l'énergie consommée est : C = Pg + Pr + Ps + R + F 100 = 4,6 + 1,6 + 0,8 + 4 8 + 45 Ce budget est comparé avec ceux d'autres gastéropodes phytophages ainsi qu'avec ceux établis pour Crassostrea gigas dans le même secteur.